Profil Penyimpanan Obat High Alert Di Instalasi Farmasi Rumah Sakit Islam At-Tin Husada Ngawi Tahun 2023 - Erika Aulia; Andita Nur Wijayanti; Diah Nurcahyani (STIKes Ibnu Sina Ajibarang, 2024)
High alert medicines are medicines that require extra vigilance as they may cause serious harm if stored or labelled incorrectly. For this reason, these medicines need to be properly monitored and managed. The objective of this study is to assess whether the management of high alert medicines in the pharmacy of Attin Husada Islamic Hospital, Ngawi Province complies with standard operating procedures (SOPs). The study employs an observational approach to assess the storage of high alert medicines against the indicators listed in the SOP compliance checklist using direct observation techniques. The study results show that the storage compliance rate of high alert medicines in the pharmacy of Attin Husada Islamic Hospital is 90,34%, considered good, and the labelling compliance rate is 57,24%, considered fair and classified as well.